Clofazimine: History and Perspectives - G. N. Mozhokina; A. G. Samoylova (Туберкулез и болезни лёгких)
The review analyses 47 publications that follow the pathway of clofazimine from its discovery to recognition as a Group B drug for treatment of multiple drug resistant tuberculosis. It describes its mechanism of action and effects on Mycobacterium tuberculosis, pharmacokinetics, and safety parameters.